Prolonged Bleeding Time, Reduced Platelet Aggregation, Altered PAF-Acether Sensitivity and Increased Platelet Mass Are a Trait of Asthma and Hay Fever - Szczeklik, A; Milner, P C; Birch, J; Watkins, J; Martin, J F (Thrombosis and Haemostasis, 1986)
In a case control study 31 asymptomatic patients with asthma and/or hay fever and 31 normal controls had their bleeding time measured using the Simplate II device and venostasis. Mean bleeding time in the atopic group (527 s) was significantly prolonged compared to the controls (393 s) (p <0.0005). Platelet aggregation to collagen and ADP (but not to PAF-acether) was significantly depressed in the atopies. Mean circulating platelet mass was significantly greater in atopies than in the controls (p = 0.006). Stepwise multiple regression analysis showed that within the control group bleeding time was best predicted by platelet mass (p = 0.007). No such relationship was found in the atopies. However stepwise multiple regression analysis showed that bleeding time in the atopies (but not in the controls) was best predicted by PAF-acether induced platelet aggregability (p <0.05). In neither group was bleeding time related to collagen induced platelet thromboxane B2 production.It is hypothesised that in respiratory atopy the depressed aggregatory function of platelets is not compensated for sufficiently by an increase in platelet mass, leading to prolongation of the bleeding time. This haemostatic imbalance, whose cause remains to be established, appears to constitute a trait of atopy.
Keywords: Bleeding time; Asthma; Platelet aggregation; PAF